2007
DOI: 10.2486/indhealth.45.160
|View full text |Cite
|
Sign up to set email alerts
|

Five-Hour Sleep Restriction for 7 Days Increases Subjective Sleepiness

Abstract: We investigated the effects of a 5-h sleep restriction for 7 d on subjective sleepiness in an ambulatory condition by comparing them with baseline conditions consisting of an 8-h sleep for 7 consecutive days. Subjects were 13 healthy male students (mean age 21.1 yr). Each subject was required to get 8 h of sleep (baseline, from 2300 to 0700) for 7 d, and 5 h of sleep (sleep restriction, from 0100 to 0600) for 7 d in an ambulatory condition. The order of the two sleep schedules was randomly assigned. Subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Under such sleep restriction conditions, we observed that subjects felt sleepy from the 4th day until the last day and this subjective complaint seems to rapidly ceil at a score of 5. These results are in line with those of previous studies (Belenky et al, 2003 ; Van Dongen et al, 2003 ; Kobayashi et al, 2007 ; Lo et al, 2012 ; Philip et al, 2012 ). In parallel, our results demonstrate that a week of severe sleep restriction (4 h of TIB) is both responsible for sustained attention deficits, with a decrease of response speed and an increase in the number of lapses, and executive disorders with an increase in the numbers of errors (“No-Go” trials) while sleepy subjects were still able to perform a sensori-motor coordination task.…”
Section: Discussionsupporting
confidence: 93%
“…Under such sleep restriction conditions, we observed that subjects felt sleepy from the 4th day until the last day and this subjective complaint seems to rapidly ceil at a score of 5. These results are in line with those of previous studies (Belenky et al, 2003 ; Van Dongen et al, 2003 ; Kobayashi et al, 2007 ; Lo et al, 2012 ; Philip et al, 2012 ). In parallel, our results demonstrate that a week of severe sleep restriction (4 h of TIB) is both responsible for sustained attention deficits, with a decrease of response speed and an increase in the number of lapses, and executive disorders with an increase in the numbers of errors (“No-Go” trials) while sleepy subjects were still able to perform a sensori-motor coordination task.…”
Section: Discussionsupporting
confidence: 93%
“…Sleep disorders may be caused by underlying emotional disorders, that is, anxiety or depression, and sleep disorder may worsen each of them (12). Sleep deprivation leads to a drop in academic performance (7), increases day-time sleepiness (13), leads to early fatigue (5), decreases alertness (14) and increases errors at work. In house officers, it affects divergent and creative thinking (15), decreases surgical dexterity (16), and increases errors in healthcare.…”
Section: Consequences Of Sleep Deprivationmentioning
confidence: 99%